All Stars Turns 61: Hell Yard Boys Look Back at the Bad Old Days - Pickford-Gordon, Lara (Trinidad Guardian)
This article tells the history of the Neal and Massy Trinidad All Stars steel orchestra, the band from Hell Yard, as they celebrate their 61st anniversary. Neville Jules, the innovator, bandleader and pan man earned the respect of all who came under his command and his contribution ranks him with Elle Mannette and Winston 'Spree' Simon.
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago -- History